2022
DOI: 10.1097/md.0000000000031860
|View full text |Cite
|
Sign up to set email alerts
|

Association between microRNA-146a rs2910164 polymorphism and coronary heart disease: An updated meta-analysis

Abstract: Background: Coronary heart disease (CHD) is one of the manifestations of atherosclerosis with a high morbidity rate. MicroRNA (miRNA)-146a rs2910164, a single nucleotide polymorphism, is associated with the progression of CHD risk. However, the results are controversial and uncertain. Therefore, an updated meta-analysis was conducted to evaluate the association between rs2910164 and CHD susceptibility.Methods: PubMed, Cochrane Library, EMBASE, Web of Science, China's National Knowledge Infrastructure, VIP, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The G allele of rs2910164 is associated with an increased risk of psoriasis [ 67 ]. Two meta-analyses concluded that it may be associated with a lower risk of CHD, but further research is needed [ 68 , 69 ].…”
Section: The Role Of Micrornas In Atherosclerosis Psoriasis T2dm and Ramentioning
confidence: 99%
“…The G allele of rs2910164 is associated with an increased risk of psoriasis [ 67 ]. Two meta-analyses concluded that it may be associated with a lower risk of CHD, but further research is needed [ 68 , 69 ].…”
Section: The Role Of Micrornas In Atherosclerosis Psoriasis T2dm and Ramentioning
confidence: 99%
“…The G allele of rs2910164 is associated with an increased risk of psoriasis [58]. Two meta-analyses concluded that it may be associated with a lower risk of CHD, but further research is needed [59,60].…”
Section: Mir-146amentioning
confidence: 99%